The emerging role of autophagy and mitophagy in tauopathies: From pathogenesis to translational implications in Alzheimer’s disease - Liu, Xiaolan; Ye, Meng; Ma, Liang (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD) is the most prevalent neurodegenerative disease, affecting more than 55 million individuals worldwide in 2021. In addition to the “amyloid hypothesis”, an increasing number of studies have demonstrated that phosphorylated tau plays an important role in AD pathogenesis. Both soluble tau oligomers and insoluble tau aggregates in the brain can induce structural and functional neuronal damage through multiple pathways, eventually leading to memory deficits and neurodegeneration. Autophagy is an important cellular response to various stress stimuli and can generally be categorized into non-selective and selective autophagy. Recent studies have indicated that both types of autophagy are involved in AD pathology. Among the several subtypes of selective autophagy, mitophagy, which mediates the selective removal of mitochondria, has attracted increasing attention because dysfunctional mitochondria have been suggested to contribute to tauopathies. In this review, we summarize the latest findings on the bidirectional association between abnormal tau proteins and defective autophagy, as well as mitophagy, which might constitute a vicious cycle in the induction of neurodegeneration. Neuroinflammation, another important feature in the pathogenesis and progression of AD, has been shown to crosstalk with autophagy and mitophagy. Additionally, we comprehensively discuss the relationship between neuroinflammation, autophagy, and mitophagy. By elucidating the underlying molecular mechanisms governing these pathologies, we highlight novel therapeutic strategies targeting autophagy, mitophagy and neuroinflammation, such as those using rapamycin, urolithin, spermidine, curcumin, nicotinamide, and actinonin, for the prevention and treatment of AD.